On conventional versus direct aging of laser-directed energy deposited Mg–6Gd–3Y–0.5Zr alloy - Yiling Jiang; Haibo Tang; Zhuo Li; Yuanhang Gao; Zhe Xu; Huaming Wang (Materials Research Letters)
Mg–Gd–Y–Zr alloys, with high Gd and Y solubility, demonstrate significant application potential due to effective precipitation strengthening but face challenges from lengthy aging times. Hereby we fabricate a Mg–6Gd–3Y–0.5Zr alloy via laser-directed energy deposition (LDED) technique. Taking the advantages of fine microstructures and supersaturation resulting from rapid solidification, direct aging (T5) can be conducted. T5 achieves peak hardness and tensile strength comparable to conventional solution and aging treatment (T6) yet in half the aging time, attributed to pipe diffusion via dislocations induced by tension–compression cycles during LDED. This study advances efficient heat treatments for LDED-fabricated precipitation-strengthening alloys.